Corporate ventriloquism undermines action on alcohol harms. (3rd August 2021) - van Schalkwyk, May C I; Maani, Nason; Pettigrew, Simone; Petticrew, Mark
Abstract : Industry, women's rights, and WHO's draft alcohol strategy